Slice blotting: a method for detecting the release of immunoreactive substances from living brain tissue - Lowe, Graeme (Journal of neuroscience methods, 1999)
The intricate circuitry of the CNS forms highly organized structures containing a multitude of transmitters, modulators and other chemical signals expressed in specific patterns and pathways. Anatomical studies with immunohistochemical and molecular biological techniques have mapped in fine detail the distribution of these substances in fixed tissue. However, the release of neuroactive substances is often under precise spatial control and is regulated by numerous physiological factors. Understanding such complex intercellular signaling systems will require the development of new spatially resolved methods for detecting secretion in living systems. A simple but powerful method is described here for visualizing and quantifying the time-integrated spatial pattern of release of chemical signals from living neural tissue. The method combines the in vitro brain slice preparation with immunostaining protocols used for antigen detection on Western blots. It has widespread potential application in biological research because it can map in vitro patterns of release of cytokines, growth factors, chemoattractants, chemorepellents, morphogens, enzymes, and other paracrine signals in spatially organized systems, subject to a variety of stimuli and conditions.